2022
DOI: 10.3389/fcimb.2022.980399
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum pepsinogens and gastrin-17 with Helicobacter pylori infection assessed by urea breath test

Abstract: BackgroundAssociation of gastric atrophy or cancer with levels of serum pepsinogens, gastrin-17 and anti-Helicobacter pylori IgG antibody have been extensively studied. However, the association of serum pepsinogen and gastrin-17 with H. pylori infection has not been studied in a large population.AimTo investigate the impact of H. pylori infection on serum levels of pepsinogens and gastrin-17.MethodsA total of 354, 972 subjects who underwent health check-ups were included. Serum levels of pepsinogens and gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…pylori infection can lead to secondary hypergastrinemia and hyperpepsinogenemia, indicating that both G-17 and PG I/II levels can re ect the presence of H. pylori infection to some extent [25][26][27]. Studies have shown that PG I and PG II levels are associated with H. pylori infection; furthermore, a close relationship between G-17 and H. pylori, as patients with H. pylori infection have signi cantly higher levels of G-17 than those without infection [28,29]. This suggests that G-17, PG I, and PG II are associated with H. pylori infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pylori infection can lead to secondary hypergastrinemia and hyperpepsinogenemia, indicating that both G-17 and PG I/II levels can re ect the presence of H. pylori infection to some extent [25][26][27]. Studies have shown that PG I and PG II levels are associated with H. pylori infection; furthermore, a close relationship between G-17 and H. pylori, as patients with H. pylori infection have signi cantly higher levels of G-17 than those without infection [28,29]. This suggests that G-17, PG I, and PG II are associated with H. pylori infections.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that G-17, PG I, and PG II are associated with H. pylori infections. As H. pylori-induced gastritis is the most common condition, these three markers not only re ect the overall gastric function but also indirectly indicate the presence of H. pylori infection in the body [23,29].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have also found that H. pylori -positive patients have significantly higher PG II levels than H. pylori -negative patients, so it can be used as a marker of active H. pylori infection [ 25–27 ]. Zhou JP also found that the level of G-17 in patients with H. pylori infection was significantly higher [ 19 ]. This is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%